PENERAPAN METODE DISKUSI DALAM MENINGKATKAN KEMAMPUAN GURU MEMANFAATKAN LINGKUNGAN SEKOLAH SEBAGAI SUMBER BELAJAR DI SD NEGERI 007 KOTA LAMA KECAMATAN RENGAT BARAT KABUPATEN INDRAGIRI HULU - Suhartatik ' (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar Fakultas Keguruan dan Ilmu Pendidikan Universitas Riau, 2017)
From preliminary observations made in SD Negeri 007 Kota Lama, teachers in these schools take advantage of the school environment as a learning resource only two to three times in one semester. Teachers are more frequently present lessons in the classroom despite the presented materials related to the school environment. From the interviews conducted prospective researchers, most of the teachers admitted reluctantly invites students to learn outside the classroom, for reasons difficult to supervise. In addition there are teachers who said that they could not and did not know in the use of the school environment as a learning resource. Based on these issues, school action research was conducted with the aim of improving the ability of teachers to utilize the school environment as a learning resource and to identify the weaknesses and strengths as discussions on the improvement of teacher's ability to utilize the school environment as a learning resource in SD Negeri 007 Kota Lama. This study was designed in the form of Action Research School planned conducted in two cycles. The subjects of this study were teachers at SD Negeri 007 Kota Lama, amounting to 18 people classroom teachers. Pursuant to the research note that there is an increase in the ability of teachers to utilize the school environment as a learning resource approach Discussion on SD Negeri 007 Kota Lama. By leveraging the advantages of discussion in the working group of teachers (KKG), will be able to solve the problems faced by teachers especially those associated with the use of the school environment as a learning resource in the teaching and learning process in SD Negeri 007 Kota Lama. Generally seen an increase in the ability of teachers in using schools as a learning resource. The increase was mainly on the ability categorized good, based on the indicators of research is also known that the ability of teachers in the second cycle reaches indicators that have been established, ie the ability of teachers are categorized either achieved amounted to 81.8%, meaning that this figure has exceeded the success rate has been set, ie 70%.